The Effect of Transformational Leadership, Job Motivation, Reward on Job Satisfaction and Job Performance - Regina Anindita; Justine Tanuwijaya (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
The study aimed to analyze the relationship among transformational leadership, motivation, and reward on job satisfaction, and also examine the effect of transformational leadership, motivation, reward, and job satisfaction on job performance in the Ministry of Industry. The population in this study are employees of the Ministry of Industry with a total of 202 employees as a sample. The determination of the sample was carried out using the non-probability sampling by purposive sampling method. The data analysis technique used is the Structural Equation Modelling (SEM) method. The technique of data collection used is by distributing questionnaires through the Google Form application. The analytical method used is SEM-PLS analysis. The results showed there was a significant effect of Transformational Leadership on Job Satisfaction. There was a significant effect of Motivation on Job Satisfaction. There was a significant effect of Reward on Job Satisfaction. There was no significant effect of Transformational Leadership on Job Performance. There was a significant effect of Motivation on Job Performance. There was a significant effect of Reward on Job Performance. There was no significant effect of Job Satisfaction on Job Performance. Transformational Leadership, motivation, and reward play essential roles to determine employee Job Satisfaction and Job Performance. Leaders can use Transformational Leadership, motivation, and reward as factors to enhance job satisfaction and job performance. Future research is expected to use mediating variables to analyze the role of job satisfaction which mediates the effect of Transformational Leadership, motivation, and reward on job performance.